DETEKSI MANIPULASI LAPORAN KEUANGAN MENGGUNAKAN BENEISH M-SCORE PADA PERUSAHAAN BUMN - Amelia, Rima; Rahman, Huda Aulia (Lembaga Penerbitan Unversitas Esa Unggul, 2024)
The aim of this research is to analyze financial statement manipulation as well as look for the influence of eight financial ratios on financial statement manipulation using the Beneish M-Score method. This research is quantitative, using secondary data. The population of this research is state-owned companies listed on the Indonesia Stock Exchange in 2021–2023. The sampling technique used was a purposive sampling method, so the number of samples was 24 state-owned companies. The data analysis methods used are descriptive statistics, logistic regression testing, and hypothesis testing using SPSS 26 software. The research results show that, partially, the DSRI and GMI variables have a positive effect on financial report manipulation, LVGI and TATA have a negative effect on financial statement manipulation, and AQI, SGI, DEPI, and SGAI have no effect on financial statement manipulation. During the 2021–2023 period, there were 25 companies in the manipulator category, while there were 47 non-manipulator companies.